2011
DOI: 10.1002/pon.1932
|View full text |Cite
|
Sign up to set email alerts
|

Implementing screening for distress, the 6th vital sign: a Canadian strategy for changing practice

Abstract: Establishing a national approach to implementing Screening for Distress is both feasible and beneficial. A coordinated approach encourages collaboration beyond the walls of any particular center and provides the opportunity for all patients to be provided with improved person-centered care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
140
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(154 citation statements)
references
References 9 publications
4
140
0
10
Order By: Relevance
“…Referral, comprehensive assessment, or intervention by a more specialized health care professional can then be arranged if necessary 1,6,7 . It has been found that, when distress screening is implemented, staff members are enthusiastic about screening and appreciate the associated training 7 .…”
Section: Screening For Distressmentioning
confidence: 99%
See 3 more Smart Citations
“…Referral, comprehensive assessment, or intervention by a more specialized health care professional can then be arranged if necessary 1,6,7 . It has been found that, when distress screening is implemented, staff members are enthusiastic about screening and appreciate the associated training 7 .…”
Section: Screening For Distressmentioning
confidence: 99%
“…Carlson et al 9 found that, despite enthusiasm, 38% of clinicians believe that screening is impractical for routine use, and 43% of nurses and radiographers rated a screening program as "not useful." And yet others argue that screening has several benefits: it allows for follow-up and coordination of appropriate services, and it increases outreach to patients 1,7,9,12,13 . Accordingly, debate is ongoing in the literature.…”
Section: Screening For Distressmentioning
confidence: 99%
See 2 more Smart Citations
“…How screening is implemented in the face of social, organizational and economic challenges [31][32][33] will be the next hurdle to overcome if psychosocial oncology is to find its place as a core program within the cancer care system worldwide.…”
mentioning
confidence: 99%